2000
DOI: 10.1101/gad.829100
|View full text |Cite
|
Sign up to set email alerts
|

Ssn6–Tup1 interacts with class I histone deacetylases required for repression

Abstract: Ssn6-Tup1 regulates multiple genes in yeast, providing a paradigm for corepressor functions. Tup1 interacts directly with histones H3 and H4, and mutation of these histones synergistically compromises Ssn6-Tup1-mediated repression. In vitro, Tup1 interacts preferentially with underacetylated isoforms of H3 and H4, suggesting that histone acetylation may modulate Tup1 functions in vivo. Here we report that histone hyperacetylation caused by combined mutations in genes encoding the histone deacetylases (HDACs) R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
155
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(164 citation statements)
references
References 39 publications
6
155
1
2
Order By: Relevance
“…Tup1 is known to alter local chromatin structure by interacting with chromatin-modifying proteins [19][20][21] , including Hda1 22 . Hda1 is a class 2 histone deacetylase required for repression of a subset of Tup1-repressed genes 23 .…”
mentioning
confidence: 99%
“…Tup1 is known to alter local chromatin structure by interacting with chromatin-modifying proteins [19][20][21] , including Hda1 22 . Hda1 is a class 2 histone deacetylase required for repression of a subset of Tup1-repressed genes 23 .…”
mentioning
confidence: 99%
“…Previous experiments have suggested that Tup1-mediated repression might also involve formation of silencing heterochromatin (18)(19)(20). These include reports that Tup1 binds histone tails along the entire length of the promoter and occludes the transcriptional machinery (18) and that Tup1 recruits a histone deacetylase activity (21). However, although the Tup1-histone tail interactions have been suggested to play a role in repression of certain promoters, others have reported that Tup1 represses significantly even where the relevant histone tails are presumably rendered nonfunctional by mutations (22,23).…”
mentioning
confidence: 99%
“…The reason the corepressor targets multiple proteins is not known, nor is it clear whether Tup1 targets all of these polymerase II-associated proteins at every promoter or whether it interacts with different targets at different promoters. Different tetratricopeptide repeats in Ssn6 are required for repression of different genes, and differential changes in H3 and H4 acetylation associated with Tup1-regulated genes have been observed (27,33). Thus, different repressive architectures may exist at different genes regulated by this corepressor.…”
Section: Discussionmentioning
confidence: 99%
“…Ssn6-Tup1 interacts physically with class I histone deacetylases (HDACs), 1 and simultaneous mutation of the three HDAC genes, RPD3, HOS1, and HOS2, abolishes repression by Ssn6-Tup1 (27). The Ssn6-Tup1 complex interacts with at least two of these HDACs, Rpd3 and Hos2 (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation